Sistem pendukung keputusan kelayakan dalam menentukan posisi jabatan pada PT SCI dengan metode FAHP - Leonardo, Leonardo (AITI, 2024)
Making decisions in giving positions to employees is important because it can affect the company's progress; the assignment itself has several types, one of which is the provision of promotions and demotions to employees. In this study, a decision support system was developed to determine employee positions by providing demotions or promotions to employees working at PT SCI using the web-based Fuzzy AHP (FAHP) method. The results are that employees in the top four ranks will get promotions, and employees with high positions but not in the top four will be demoted. The data collected is PT SCI's employee data. The results of this research are decision-making applications using the FAHP methods, which can help simplify and speed up the determination of employee demotions and promotions.